1994
DOI: 10.1042/bj3010495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tri-iodothyronine administration on the disposal of oral [1-14C]triolein, lipoprotein lipase activity and lipogenesis in the rat during lactation and on removal of the litter

Abstract: The effect of tri-iodothyronine (T3) administration on the utilization of dietary [14C]lipid by the mammary gland and adipose tissue of lactating and litter-removed rats was studied. (1) After an oral load of [1-14C]triolein, the lactating rats treated with T3 (50 micrograms/100 g body wt.) over 24 h showed an increase in 14CO2 production and a decrease in the total [14C]lipid transferred through the mammary gland that was paralleled by a decrease in tissue lipoprotein lipase (LPL) activity. (2) T3 administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
2
1
0
Order By: Relevance
“…Similar conclusions may be attained when analyzing the data found at midlactation in the litter removed rat. In agreement with previous reports, 30,39 LPL activity greatly declined in the mammary gland, whereas it increased in lumbar adipose tissue. Plasma triglyceride levels greatly increased in these animals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar conclusions may be attained when analyzing the data found at midlactation in the litter removed rat. In agreement with previous reports, 30,39 LPL activity greatly declined in the mammary gland, whereas it increased in lumbar adipose tissue. Plasma triglyceride levels greatly increased in these animals.…”
Section: Discussionsupporting
confidence: 93%
“…[27][28][29] Therefore, the present study was undertaken to determine the potential relationship between changes in LPL activity in adipose tissue and the mammary gland as compared with their content of ␣-tocopherol during late gestation and midlactation in the rat. Because litter separation at midlactation causes an abrupt and opposite change in LPL activity in the mammary gland and adipose tissue, [30][31][32] this strategy was also used to determine its effect on ␣-tocopherol content in these tissues. Results show that around parturition and during lactation in the rat, changes in ␣-tocopherol content in the mammary gland correlate with tissue LPL activity, suggesting a direct relationship, whereas this is not the case in adipose tissue, where major changes in LPL activity are not followed by parallel changes in its content of ␣-tocopherol.…”
mentioning
confidence: 99%
“…This is consistent with the linear relationship that has been reported between TG secretion rate and plasma TG concentration, after presumed blockade of peripheral TG clearance by Triton WR1339, in rats with increasing concentrations of plasma L-T4 [22]. Additionally, it has been shown that the administration of 50 ig/100 g body weight of 14 causes diminution of lipoprotein lipase activity in both mammary gland and adipose tissue [23]. A decreased activity of lipoprotein Iipase in peripheral tissues also could contribute to the higher levels of triglyceride in serum of chronic hyperthyroid rats.…”
Section: Discussionsupporting
confidence: 90%